Witch-mother is which? The potential role of the analyst in facilitating authentic motherhood. (2nd January 2017) - Schechter, Daniel S.
Abstract: This paper explores challenges in the treatment of women suffering from disturbances in maternal identification. A review of the psychoanalytic and developmental literature focuses on the frequent finding of early-onset mother–daughter relational disturbance involving maternal narcissistic fragility and exaggerated dependency needs, intergenerational trauma, and related psychopathology including mutual affect dysregulation. A case example of a young woman with a severe anxiety disorder is presented and discussed to illustrate the challenges to the traditional psychoanalytic technique. This patient avoided pregnancy into her late thirties and entered analysis with feelings of inauthenticity, characterological masochism, and a "secret mission" to unmask the witch recurring in her dreams. Through an elaborate working-through of negative maternal transference, the analyst and patient saw through the birth of the patient's authentic self, a new approach to her career, her relationships with men, and her anticipation of the birth of a child by the sixth year of treatment. The author posits that psychoanalytic technique benefits from contemporary, attachment, and trauma research that supports the analyst's playing a more active role in approaching, co-regulating, tolerating, and integrating avoided affects and memory traces that are associated with early-onset relational disturbances worsened by the effects of violence, maltreatment, and loss.